PERIODONTAL DISEASE AND COMPLICATIONS IN THE CONTEXT OF THE COVID-19 PANDEMIC. INACTIVATION OF PATHOGENS AT THE LEVEL OF A DENTAL OFFICE IN THE CONTEXT OF THE PANDEMIC. REVIEW. - Ionuț-Daniel Gafincu-Grigoriu; Liliana Pasarin; Ana-Emanuela Botez; Doinita Temelie-Olinici; Ionut-Catalin Botezatu; Darius Sandu; Ruxandra Stan; Carmen Elena Cotrutz (Romanian Journal of Medical and Dental Education, 2023)
When a disease is new to humans, only very few people are immune to it. In such cases, there is no vaccine and the result can be a rapid increase in the incidence of the disease. How dangerous or deadly that disease is – it all depends on the specific virus in question and the general state of health of each individual patient. If a disease does not only spread regionally but ends up affecting entire countries and continents, then experts speak of a pandemic.